Green technology extraction of Dictyophora indusiata at the egg stage: Unveiling the antioxidant potential and bioactive components for cosmetic applications - Prathumtet, Jatuporn; Kumlung, Tantima; Sila-On, Warisada; Puapermpoonsiri, Utsana (Science, Engineering and Health Studies, 2025)
Mushrooms have been introduced as potential sources of natural antioxidants. Different bioactive components and antioxidant activity have been reported for different extraction methods. Therefore, this study aimed to examine the bioactive components and antioxidant activity of Dictyophora indusiata in eggs extracted with water using microwave-assisted extraction (MAE), ultrasonic-assisted extraction (UAE), and hot water extraction (HWE). The results indicated that the extract yields ranged from 12.33 ± 0.42% to 15.60 ± 1.44%. UAE exhibited the strongest antioxidant activity in the 2,2’-azinobis (3-ethylbenzthiazoline-6-acid) assay (IC50 of 5.68 ± 0.09 mg/mL), whereas HWE demonstrated the best antioxidant activity in both the 2,2-diphenyl-1-picrylhydrazyl assay and the ferric reducing antioxidant power assay. Furthermore, the MAE yielded the highest total polysaccharide content (746.75 ± 3.04 mg glucose/g extract). The highest total phenolic content (9.73 ± 0.28 mg gallic acid/g extract) was observed in UAE. The total flavonoid content, a subtype of phenolic compounds, was enriched in HWE and UAE (3.96 ± 0.03 and 3.96 ± 0.12 mg quercetin/g extract, respectively). In summary, UAE was shown to be a promising method for extracting bioactive components with antioxidant activity, offering advantages in reducing extraction time and temperature, which is appropriate for cosmeceutical applications.